Towards the detection of tonotopic reorganisation in the human auditory cortex - Gurer, Benjamin Jason (2020)
Peripheral hearing loss not only causes a reduction in hearing sensitivity (increase in hearing threshold) but also leads to problems in suprathreshold hearing – such as difficulty understanding speech in noise – and is often associated with tinnitus. Animal research has suggested that such impairments may be related to changes in central auditory processing arising as a consequence of a reduction in peripheral auditory output (Norena and Farley 2013). The auditory cortex is tonotopically organised, with neighbouring parts of the cortex responding to neighbouring frequencies. In animals, peripheral hearing loss has been shown to cause large-scale tonotopic reorganisation in auditory cortex, whereby neurons responsive to frequencies affected by the hearing loss (typically higher frequencies), shift their tuning towards less affected (lower) frequencies.